The Relationship Between Work-life Balance and OrganizationalSupport Towards Happiness at Work of Nurses at the Public Hospitals Located at the Suburb Area of Bangkok - Churchinnawong, Wannisa; Apiruknapanond, Panta (Journal of health and health management, 2025)
The objective of this descriptive research was to study the level of balance between personal life and work, organizational support and happiness in working of the professional nurses in hospitals around Bangkok’s perimeter in order to find out the relationship between the balance of personal life and work, organizational support and happiness in working of the professional nurses in hospitals around Bangkok’s perimeter. The sample group was professional nurses who had work experience of 1 year or more with the exception of professional nurses who were in executive positions working in these three hospitals around Bangkok’s perimeter namely Samutprakan Hospital, Pathumthani Hospital and Samutsakhon Hospital. G* power program was being applied to find out sample values using multi-stage random sampling, resulting a sample size of 152 people. The research instruments consisted of personal information questionnaire, questionnaire about the balance of personal life and work, questionnaire about organizational support, and work happiness questionnaire. The reliability values were equal to 0.91-0.92 and 0.97 respectively. Data were analyzed by calculating the average, standard deviation and Pearson’s correlation coefficient. The research results were the level of personal life and work balance of professional nurses in hospitals around Bangkok’s perimeter was overall at a high level ( =2.74, SD=.49). The overall level of organizational support of professional nurses in hospitals around Bangkok’s perimeter was high ( =2.94, SD=.50). The level of happiness at work in hospitals around Bangkok’s perimeter was high ( = 3.22, SD=.40). The personal life balance with work and organizational support had a positive relationship with happiness at work of the professional nurses in hospitals around Bangkok’s perimeter with statistical significance at the .01 level (r=.45 and r=.66).